TANTANGAN DAN PELUANG LEMBAGA PENDIDIKAN ISLAM DI ERA MASYARAKAT EKONOMI ASEAN (MEA) - San Putra; Arif Rahman; Maslina Siagian; Jamal Thahir Karo Karo (Sekolah Tinggi Agama Islam Al Hidayah, 2015)
Globalization era is problem for everybody in the world. The impact of globalization are no limit among nations, so open and transparant. It cause positive and negative impact. Indonesia as member of ASEAN Economic Community (AEC) at December, 31, 2015. AEC can give competition at ASEAN. AEC can give benefit for member of ASEAN. This situation give threath and opportunity for education institution in Indonesia. At AEC era, all of information cause big impact. Information technology change thinking, life style and social culture. West culture change thinking, culture and character of Indonesian people. Education as effective media build quality of human resource. Education is very important for build human resource and develop nation character. Globalization in education build up sources of learning and social media as internet and electronic media. They are as source of knowledge and center of education. The impact of social media in learning system, teacher is not just source of knowledge. Student can get knowledge from information technology. Negative impact from globalization are battle of student, free sex and crime. It is very important for optimalization of education to look for solution from this problem. Eduacation institution must be as last stronghold to fight negative impact from communication and information technology.Keyword: Globalisasi, Peluang, Tantangan, Pendidikan.